Synthesis of CdFe2O4-SnO2 Nano Spinel Ferrite and Investigation of the Structural and H2S Gas Sensing Properties - Abd Alkareem, Mariam O.; Al-Saadi, Tagreed M. (Iraqi Journal of Science, 2026)
In this paper, nanoferrite (CdFe2O4-SnO2) was prepared by the auto combustion method (sol-gel), with weight ratios of (x = 0.0, 0.05, 0.10, 0.15, 0.20, 0.25) for SnO2. The properties of the nanoferrite were characterized by XRD, FE-SEM, and EDX techniques. The results showed that the produced compound had a cubic spinel ferrite phase; the crystallite size was determined using the Scherrer and Williamson-Hall equation. The FE-SEM image demonstrated that the compound is porous, with nanoscale particles that have a ball-like appearance. The EDX test verified the existence of Fe, O, Cd, and Sn atoms. Gas sensing showed the compound's high sensitivity to H2S.